Calcium Handling Defects and Cardiac Arrhythmia Syndromes - Kistamás, Kornél; Veress, Roland; Horváth, Balázs; Bányász, Tamás; Nánási, Péter P.; Eisner, David A. (Frontiers in Pharmacology, 2020)
Calcium ions (Ca2+) play a major role in the cardiac excitation-contraction coupling. Intracellular Ca2+ concentration increases during systole and falls in diastole thereby determining cardiac contraction and relaxation. Normal cardiac function also requires perfect organization of the ion currents at the cellular level to drive action potentials and to maintain action potential propagation and electrical homogeneity at the tissue level. Any imbalance in Ca2+ homeostasis of a cardiac myocyte can lead to electrical disturbances. This review aims to discuss cardiac physiology and pathophysiology from the elementary membrane processes that can cause the electrical instability of the ventricular myocytes through intracellular Ca2+ handling maladies to inherited and acquired arrhythmias. Finally, the paper will discuss the current therapeutic approaches targeting cardiac arrhythmias.